State-Wide Utilization and Performance of Traditional and Cell-Free DNA-Based Prenatal Testing Pathways: The Victorian Perinatal Record Linkage (PeRL) Study. Issue 1 (January 2021) - Lindquist, A.; Hui, L.; Poulton, A.; Kluckow, E.; Hutchinson, B.; Pertile, M. D.; Bonacquisto, L.; Gugasyan, L.; Kulkarni, A.; Harraway, J.; Howden, A.; McCoy, R.; et al.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2020;56:215–224) In recent years, the use of combined first-trimester screening (CFTS) and cell-free DNA (cfDNA) screening has increased. With the rise of CFTS and cfDNA prenatal testing, there has been a dramatic decrease in the number of invasive diagnostic tests performed during pregnancy.